HOLA! HABLO ESPANOL - Nurul Sabrina Zan (Penerbit UTHM, 2010)
This book is designed for peoples who native language is not Spanish. This book also covers basic grammar, vocabulary, verb conjugation, comprehension, dialogues, etc. Furthermore, it contains exercises that are believed to help fresh learners to better understand the language. Among the features of this book include the alphabets, talking about personal information, common phrases in classroom, exchanging greetings, recognize and properly use nouns, verbs and adjectives.